2013
DOI: 10.1002/ana.23814
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic involvement in patients with neurologic impairment due to Shiga toxin 2

Abstract: These findings suggest that the direct cytotoxic effect of Shiga toxin 2 in the thalamus might contribute to the pathophysiology of neuronal complications in hemolytic-uremic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…It comprises acute kidney injury, thrombocytopenia (platelet count b 150.000 cells/mm 3 ), and microangiopathic hemolytic anemia [2]. HUS is the most common cause of acute renal failure in childhood [3][4][5][6][7] and occurs predominantly in children younger than five years [2,[6][7][8][9][10][11]. Between May and July 2011, the world's largest reported HUS outbreak affected northern Germany [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It comprises acute kidney injury, thrombocytopenia (platelet count b 150.000 cells/mm 3 ), and microangiopathic hemolytic anemia [2]. HUS is the most common cause of acute renal failure in childhood [3][4][5][6][7] and occurs predominantly in children younger than five years [2,[6][7][8][9][10][11]. Between May and July 2011, the world's largest reported HUS outbreak affected northern Germany [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the following pathomechanisms have also been proposed: metabolic (azotaemia, hyponatremia with consequent osmotic derangements, and demyelination) [16], inflammatory [10,18], mixed toxic-inflammatory [11,14], mixed toxic-metabolic [8,19,20], and direct toxic effects [16]. However, the possibility that Stx may have a direct influence on neurons has not been systematically analyzed [9]. Recently, based on combinations of different experiments in Long-Evans rats, Meuth et al found an enhanced expression of Gb3 receptors on thalamic neurons of female rats compared to other brain regions and to male animals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations